Study the effect of some plants extracts on growth of Mycobacterium tuberculosis in Comparison with Ethambutol - Abbas, Maysoon Sabah (The Iraqi Journal of Veterinary Medicine, 2011)
This study was conducted to investigate the inhibition role of alcoholic extracts of plants Trigonella foenumgraecum , Piper cubeba , Piper nigrum, Camphora , Commiphora molmol, Apium graveolens , Arachis hypogaea , Linum usitatissumun , Cuminum cyminum , Pimpinella anisum , Lepidium sativum , alcoholic extracts of plants used was prepared and used of concentration 200 mg/ml and add 0.2 ml of each extracts to 10 ml of media and 0.2 ml of Ethambutol to 10 ml of media the drug for mycobacteria and media with out any adding for controls. Cultural media were inoculated with 3 drops of bacterial suspension ( 1mg /ml ) in concentration 108 cfu/ml from patient suffering from tuberculosis and after incubation on 37 °C the result read weekly up to 4 weeks . the results showed good growth on the control slopes , which was evident within 2-3 weeks and no growth on the cultural media contain (Arachis hypogea , Cuminum cyminum , Commiphora molmol, Trigonella foenumgraecum , Lepidium sativum , Ethambutol ) it while the media contain (Piper nigrum , Pimpinella anisum showed than 5 colonies the growth inhibition was recorded that means sensitivity of mycobacteria to the extracts mention above, while media contain (Piper cubeba , Camphora , Apium graveolens ). showed growth more than 5 colonies and media contain Linum usitatissumun showed good growth which means resistant of mycobacteria to the extract mentioned above .